Effective Synthesis of α‐d‐GlcN‐(1→4)‐d‐GlcA/l‐IdoA Glycosidic Linkage under Gold(I) Catalysis. Issue 8 (29th May 2015) - Li, Jiakun; Dai, Yuanwei; Li, Wei; Laval, Stéphane; Xu, Peng; Yu, Biao
Abstract An effective glycosylation procedure for the stereoselective construction of the α‐d‐GlcN‐(1→4)‐d‐GlcA/l‐IdoA glycosidic linkage found in heparin and heparan sulfate is reported. The condensation occurs between 2‐deoxy‐2‐azido‐d‐glucopyranosyl (d‐GlcN) ortho‐hexynylbenzoate donors and uronate acceptors (d‐GlcA/l‐IdoA) under mild gold(I)‐catalyzed conditions. Optimal results are obtained when performing the reaction in CH2Cl2, from −72 °C to room temperature in the presence of 4 Å molecular sieves and under the promotion of [Ph3PAuCl]/AgOTf or [(1, 1‐bis‐(diphenylphosphino)methane)(AuCl)2]/AgOTf as a source of the gold(I) catalyst. A donor/acceptor ratio of 3:1 as well as a loading of 0.6 equivalents of the gold(I) catalyst are essential to attain high yields and α selectivity, particularly for the [1+1] and [1+2] glycosylations.